Temperature Effects on Retention and Separation of PAHs in Reversed-Phase Liquid Chromatography Using Columns Packed with Fully Porous and Core-Shell Particles - Christophe Waterlot; Anaïs Goulas (Journal of Chemistry)
Effects of temperature on the reversed-phase chromatographic behavior of PAHs were investigated on three columns. The first was the recent C18 column (250 mm × 4.6 mm) packed with 5 µm core-shell particles while the others were more conventional C18 columns (250 mm × 4.6 mm) packed with fully porous particles. Among the 16 PAHs studied, special attention has been paid to two pairs of PAHs, fluorene/acenaphthene and chrysene/benzo[a]anthracene, which often present coeluting problems. Due to the low surface area of the core-shell particles, lowest retention time of each PAH was highlighted and effects of the temperature on the separation of PAHs were negligible in regard to those using columns packed with fully porous particles. For each PAH studied, it was demonstrated that peaks were symmetrical and may be considered as Gaussian peaks when the column packed with core-shell particle was employed. In the best condition, the separation of PAHs was conducted at 16°C under very low pressure values (670–950 psi = 46–65 bars). Depending on PAHs, the limit of detection ranged from 0.88 to 9.16 μg L−1. Analysis of spiked acetonitrile samples with PAHs at 10 and 50 µg L−1 and tap water at 10 µg L−1 gave very good recoveries (94%–109.3%) and high precision (1.1%–3.5%).